Empowerment of Farmers' Resources as an Effort to Prevent and Address Food Insecurity in Mamuju Tengah Regency - Asmira DM; Syahruddin Hattab; M.Nur Alamsyah; Ikhtiar Hatta (UIN Sunan Gunung Djati, 2025)
This study aims to examine how the empowerment of farmers' human resources (HR) is carried out as an effort to prevent and address food insecurity in Mamuju Tengah Regency. A qualitative approach was used. Qualitative research involves methods to explore and understand the meaning that individuals or groups assign to social issues. The data used include both primary and secondary sources. Data collection techniques involved observation, interviews, and documentation. Informants were selected using a purposive sampling technique. Data analysis followed the Miles, Huberman, and Saldana model, which consists of data collection, data display, data condensation, and conclusion drawing. Based on the research findings, it is concluded that the empowerment of farmers’ human resources as an effort to prevent and address food insecurity in Mamuju Tengah Regency has been implemented but is not yet optimal. Improvements are needed, especially in farmer involvement in decision-making, provision of training based on farmers’ actual needs, building cross-sectoral networks, and structured evaluation through training programs. The aspect of accountability in the empowerment process has not been fully applied. This stage should focus on assisting farmers in managing workloads, establishing clear standards and performance indicators for HR empowerment, and ensuring continuity in implementation.